Applicazioni di Structure from Motion (SFM) e realizzazioni di fotopiani georeferenziati nell'ambito dell'archeologia d'emergenza. - Fortunati, Maria; Simone Zopfi, Laura; Bishop, Jim; De Rosa, Alessandro; Malaspina, Fabio; Zanni, Sara (Archeomatica, 2014)
In recent years, much of the archaeological intervetions have been executed in the context of public works. To operate in such an environment involves the ability to interact synergistically with other professionals, a combination of a high level of quality in the documentation and the rapid executio of all the necessary archaeological operations. The scientific representation and publication of the data could be affected by the requirements imposed by the works' timing, in particular the graphic and topographical survey of complex structures. In recent years, new technologie have come to help the archaeologists, and they enable the reduction of the time necessary to the graphic representation of the archaeological remains, while ensuring the highest scientific level. It is possible to obtain excellent results through the use of new open-source technologies, that are also a great tool to implement a synergistic collaboration with other professionals with which the archaeologists are confronted daily. This paper presents the use of a set of open-source tools in commercial archaeology and public works, to shorten the time necessary for the surveys and improve also the quality of the results, allowing the collection of new important data.